A numerical study of the spectrum of the nonlinear Schrodinger equation - Olivier, Carel Petrus (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Mathematical Sciences. Applied Mathematics))--Stellenbosch University, 2008.